An efficient synthesis of pyrrolo2,3-dpyrimidines via inverse electron demand diels-alder reactions of 2-amino-4-cyanopyrroles with 1,3,5-triazines - Dang, Qun; Gomez-Galeno, Jorge E (Journal of organic chemistry, 2002)
The scope of the inverse electron demand Diels-Alder reaction of 2-amino-4-cyanopyrroles (3a-e) with 1,3,5-triazines (1, 2) is reported. This methodology is suitable for one-pot syntheses of highly substituted and highly functionalized pyrrolo[2,3-d]pyrimidines that are the central heterocyclic nucleus of various nucleoside natural products such as toyocamycin, sangivamycin, and tubercidin.The scope of the inverse electron demand Diels-Alder reaction of 2-amino-4-cyanopyrroles (3a-e) with 1,3,5-triazines (1, 2) is reported. This methodology is suitable for one-pot syntheses of highly substituted and highly functionalized pyrrolo[2,3-d]pyrimidines that are the central heterocyclic nucleus of various nucleoside natural products such as toyocamycin, sangivamycin, and tubercidin.